Analysis of the Relationship of the Characteristics, Knowledge And Attitude of the Midwife With Completion of Partograph Filling in Normal Delivery Care - Lubis , Ayu Ulfah Nur; Lubis, Desi Handayani; Harahap, Seri Wahyuni (PT Inovasi Pratama Internasional, 2022)
Partograph used for early detection of problems and complications in childbirth. Results of preliminary study through interviews obtained 80% of midwives who apply partograf,midwives who apply 30% for claiming the cost of labor by social asurance filling properly, 20% apply partograf by in complete filling, 30% apply partograf but filling is wrong, and 20% is not filling the partograf. The population is all midwives in health centers totaled 84 Padangmatinggi midwife, sampling technique was total population. The data was collected by using a validated questionnaire, secondary data from public health center, partograf sheet documenting data of health centers of Padangmatinggi. Analysis of the data through univariate analysis and a bivariate analysis using Chi-square test and logistic regression. There is correlation between work period (p=0.008;RP=1,504), employee status (p=0.013;RP=1,487), knowledge (p = 0.000; RP = 5.667), attitude (p = 0.000; RP = 7.222) with a completeness filling of partograf in normal delivery care. Attitude (p=0.001;RP=67.019) was the variable most strongly correlation.